A note to CEOs and boards on the recruitment of a sporting director - Parnell, D. (Academia, 2018)
In a bid to support CEOs and Boards I have developed a generic preliminary job description / specification to share freely. Please note: this is by no means final or set in stone and I am sure some will say this argue this role is too much for one person, so remember its just a generic guide on the recruitment of a Sporting Director! Furthermore, we all know each club is unique in its ownership and organisational structure so will have its own ways, but I hope it serves to generate discussion and debate across decision makers for more effective recruitment, greater clarity and clearer communication surrounding football leadership appointments.